PTU-127 Resource Use Associated With Hepatic Encephalopathy In Patients With Severe Liver Disease. (9th June 2014) - Orr, J; Morgan, CL; Hudson, M; Jenkins-Jones, S; Conway, P; Radwan, A; Currie, CJ
Abstract : Introduction: Overt hepatic encephalopathy (HE) is associated with frequent hospitalisations which are expensive to manage and result in poor quality of life. The aim was to estimate the resource use associated with HE and hospitalisation in the UK. Methods: The Clinical Practice Research Datalink (CPRD) with linked hospital data from Health Episode Statistics (HES) was used to identify patients with a first diagnosis of liver disease between 1998 and 2012 and examine their all-cause hospitalisations. HE patients were matched to controls at a ratio of 1:1 by age, gender, year of diagnosis, duration and severity of liver disease. Hospital admission data (frequency and length of stay) were characterised from HES. Admissions associated with the index diagnosis of HE were excluded. Results: 17, 030 patients were identified with an incident diagnosis of liver disease, of whom 551 (3.2%) had a recorded diagnosis of HE. 389 patients (70.6%) could be matched to non-HE controls. Total number of primarily liver-related admissions was greater in the HE group with a crude admission ratio of 3.588 (95% CI 3.085–4.173; p < 0.001). In the HE group, a significantly greater proportion of liver-related admissions were through AandE (62.1% vs. 50.0%, p < 0.001) and mean length of stay was 8.0 days (sd 11.6) vs 6.8 days (sd 9.5) (p = 0.148) in the non-HE group. Following first HE event, patients had 18.2 primary care contacts per patient year compared with 8.7 for non-HE controls (p < 0.001). Conclusion: HE was associated with increased risk of liver-related hospital admissions and increased GP attendances. Disclosure of Interest: J. Orr: None Declared, C. Morgan Consultant for: Norgine;, M. Hudson: None Declared, S. Jenkins-Jones Consultant for: Norgine, P. Conway Employee of: Norgine, A. Radwan Employee of: Norgine, C. Currie Consultant for: Norgine.